China's Macroeconomic Outlook Quarterly Forecast and Analysis Report, September 2012 - CMR of Xiamen University. (Current Chinese Economic Report Series, 2013)
Owing to the decline in domestic investment and trade with the rest of the world, China’s real GDP in the first half of 2012 was lower than expected. Based on forecasts from China’s Quarterly Macroeconomic Model (CQMM), the slowdown of the growth rate in 2013 will be moderate as a result of modestly proactive macro control policy. GDP would grow at 8.01 percent in 2012, and then rebound to 8.29 in 2013; CPI would fall to a 2.9 percent in 2012, and then would pick up to 3.27 percent in 2013. In the scenario in which the sovereign debt crisis in the euro area worsened in the second half of 2012, real GDP is forecast at 7.71 percent for 2012 and 7.5 percent for 2013. Even if the external economic environment becomes worse, China’s growth is expected to stay at above 7.5 percent, which might be a steady growth rate for the near future. If China plans to achieve a higher growth rate by launching the “2 trillion massive investment package”, the growth rate of GDP could be increased to 8.25 and 8.86 percent in 2012 and 2013 with a risk of inflation and worsening economic structure. The policy implication from CQMM: on one hand the Chinese government should be able to maintain the growth rate of around 8 percent by means of timely fine-tuning of monetary policies; on the other hand, the emphasis of the micro control should be placed on structural adjustments through fiscal policies. In the long run, deepening economic, social and institutional reform will be crucial to remove the significant structural imbalance and institutional barriers to market competition, to accelerate the transformation of economic development patterns, and finally to maintain a sustainable growth rate.  .